FAHM AL-QURâAN AL-HAKIM; TAFSIR KRONOLOGIS ALA MUHAMMAD ABID AL-JABIRI - Nadhiroh, Wardatun (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
In general, most of Qurâanic interpretations (Kitab-kitab Tafsir, red-) have a systematic of Qurâanic order in Mushaf, started from Surah al-FÃ¢tihah and ended at Surah al-NÃ¢s. Unlike those, Muhammad Abid al-Jabiri, is commonly known as al-Jabiri, contemporary Islamic thinker from Marroco, wrote a Qurâanic interpretation based on chronological order of Surahs, Fahm al-QurâÃ¢n al-HÃ¢kim. It is started from Surah al-Alaq: 1-5 and ended at Surah al-Nashr. Al-Jabiri offered new methodology to understand Qurâanic text which he called as al-fashl to answer problems of objectivity and al-washl to answer problems of rasionality. He based his interpretation on QirÃ¢âah MuÃ¢shirah (contemporary reading) so Qurâanic text will be contemporary for itself and contemporary for its readers in contemporary context. This article describes briefly about al-Jabiriâs works, Fahm al-QurâÃ¢n al-HÃ¢kim, his thoughts in Qurâanic issues and his offered interpretation methodology.